Bmal1 in Perivascular Adipose Tissue Regulates Resting-Phase Blood Pressure Through Transcriptional Regulation of Angiotensinogen. Issue 1 (3rd July 2018) - Chang, Lin; Xiong, Wenhao; Zhao, Xiangjie; Fan, Yanbo; Guo, Yanhong; Garcia-Barrio, Minerva; Zhang, Jifeng; Jiang, Zhisheng; Lin, Jiandie D.; Chen, Y. Eugene
Abstract : Background: The perivascular adipose tissue (PVAT) surrounding vessels constitutes a distinct functional integral layer of the vasculature required to preserve vascular tone under physiological conditions. However, there is little information on the relationship between PVAT and blood pressure regulation, including its potential contributions to circadian blood pressure variation. Methods: Using unique brown adipocyte–specific aryl hydrocarbon receptor nuclear translocator-like protein 1 (Bmal1) and angiotensinogen knockout mice, we determined the vasoactivity of homogenized PVAT in aortic rings and how brown adipocyte peripheral expression of Bmal1 and angiotensinogen in PVAT regulates the amplitude of diurnal change in blood pressure in mice. Results: We uncovered a peripheral clock in PVAT and demonstrated that loss of Bmal1 in PVAT reduces blood pressure in mice during the resting phase, leading to a superdipper phenotype. PVAT extracts from wild-type mice significantly induced contractility of isolated aortic rings in vitro in an endothelium-independent manner. This property was impaired in PVAT from brown adipocyte–selective Bmal1-deficient (BA-Bmal1-KO) mice. The PVAT contractile properties were mediated by local angiotensin II, operating through angiotensin II type 1 receptor–dependent signaling in the isolated vessels and linked to PVAT circadian regulation of angiotensinogen. Indeed, angiotensinogen mRNA and angiotensin II levels in PVAT of BA-Bmal1-KO mice were significantly reduced. Systemic infusion of angiotensin II, in turn, reduced Bmal1 expression in PVAT while eliminating the hypotensive phenotype during the resting phase in BA-Bmal1-KO mice. Angiotensinogen, highly expressed in PVAT, shows circadian expression in PVAT, and selective deletion of angiotensinogen in brown adipocytes recapitulates the phenotype of selective deletion of Bmal1 in brown adipocytes. Furthermore, angiotensinogen is a transcriptional target of Bmal1 in PVAT. Conclusions: These data indicate that local Bmal1 in PVAT regulates angiotensinogen expression and the ensuing increase in angiotensin II, which acts on smooth muscle cells in the vessel walls to regulate vasoactivity and blood pressure in a circadian fashion during the resting phase. These findings will contribute to a better understanding of the cardiovascular complications of circadian disorders, alterations in the circadian dipping phenotype, and cross-talk between systemic and peripheral regulation of blood pressure. Abstract : Supplemental Digital Content is available in the text.